The Influence of Self-Regulated Learning and Digital Literacy on Students' Academic Achievement - Tomi Apra Santosa; Busnawir Busnawir; Ilwandri Ilwandri; Heppy Sopacua; Andri Kurniawan (ANTHOR: Education and Learning Journal, 2026)
The development of digital technology has changed the learning paradigm in higher education, requiring students to possess adequate self-regulated learning (SRL) and digital literacy skills to support academic success. Self-regulated learning enables students to manage their learning process independently through planning, monitoring, and evaluating learning, while digital literacy plays a role in the ability to access, evaluate, and utilize digital information effectively. However, there are still variations in student academic achievement, which are suspected to be influenced by differences in SRL and digital literacy levels. This study aims to analyze the influence of self-regulated learning and digital literacy on student academic achievement. This study aims to analyze the influence of self-regulated learning and digital literacy on student academic achievement. This study uses a quantitative approach with an explanatory survey design. The study population was undergraduate students at a university in Indonesia. A sample of 250 students was selected using a proportionate stratified random sampling technique. Data were collected through a questionnaire that had been tested for validity and reliability. The self-regulated learning variable was measured through aspects of planning, self-control, and self-evaluation, while digital literacy was measured through the ability to access information, evaluate information, digital communication, and digital security. Academic achievement was measured using the Grade Point Average (GPA). Data analysis was performed using multiple linear regression at a 5% significance level. The results showed that self-regulated learning had a positive and significant effect on student academic achievement (β = 0.421; p < 0.001). Digital literacy also had a positive and significant effect on student academic achievement (β = 0.367; p < 0.001). Simultaneously, self-regulated learning and digital literacy contributed 58.4% to the variation in student academic achievement (R² = 0.584; p < 0.001). These findings indicate that students with good self-regulation skills and high digital literacy tend to have more optimal academic achievement.